Investigating the Relationship between Structural Empowerment and Resistance to Change in Iran Air - Shahmirzady, Mojtaba Rezaei (International Journal of Psychosocial Rehabilitation, 2020)
Development of the air transportation industry in the world is one of the most important components of development and growth in developed and developing countries. According to experts, Air Transportation Industry of Iran has structural problems and it is necessary to reform the traditional structure and reduce government ownership. Iran Air, the Airline of the Islamic Republic of Iran, as the oldest aviation organization of Iran is not an exception in this regard and reforming its structure to survive is inevitable. Thus, the aim of this study was to investigate the relationship between structural empowerment and resistance to change in Iran Air. The present research method is a non-experimental survey. It is also considered as an applied and correlational research in terms of objective. The statistical population is composed of middle managers of Iran Air Company. To achieve the needed data, questionnaire-based methods, library studies, and references. The used questionnaires were standard and their reliability were confirmed by industry professors and experts. According to the statistical population, 190 questionnaires were distributed and finally 160 questionnaires were completed and analyzed. To test the hypotheses of this research, structural equations modeling based on variance or partial least squares (PLS) method was used. The research results show that there is generally a negative correlation between structural empowerment and resistance to change.